1997
DOI: 10.1029/96rs03885
|View full text |Cite
|
Sign up to set email alerts
|

Cross correlations and cross spectra for spaced antenna wind profilers: 2. Algorithms to estimate wind and turbulence

Abstract: Abstract. In part 1 of this paper we developed analytic relationships linking the cross correlation and cross spectrum of the echoes from a spaced antenna system to the properties of a horizontally isotropic scattering medium (e.g., clear-air refractive index irregularities) and the background flow (e.g., laminar or isotropic turbulent flow). Using these analytic expressions, in the present paper, part 2, we construct algorithms (for both the time domain and frequency domain) for extracting unbiased wind and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
0
53
0
1
Order By: Relevance
“…This has some advantages, but the simple implementation of the technique at MF does not appear to be as robust as the FCA (Holdsworth and Reid 1997). Further development of the technique is described by Holloway et al (1997) and by Venkatesh and Frasier (2013).…”
Section: Full Spectral Analysis (Fsa)mentioning
confidence: 99%
See 2 more Smart Citations
“…This has some advantages, but the simple implementation of the technique at MF does not appear to be as robust as the FCA (Holdsworth and Reid 1997). Further development of the technique is described by Holloway et al (1997) and by Venkatesh and Frasier (2013).…”
Section: Full Spectral Analysis (Fsa)mentioning
confidence: 99%
“…Other analysis approaches to SA data are described by Lataitis et al (1995), Doviak et al (1996), and Holloway et al (1997). Lataitis et al (1995) showed that the slope of the cross-correlation amplitude at zero lag, normalized by the level of the cross-correlation amplitude at zero lag, is directly proportional to the component of the wind velocity along the antenna pair baseline.…”
Section: Lataitis Slope Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the turbulent medium can therefore not be measured. A different development, such as that by Doviak et al [1996] and Holloway et al [1997aHolloway et al [ , 1997b, is based on a description of the physical process of scattering in the antenna beam volume Liu et al [1990], and relates the spatial spectrum of the scatterers to the cross-correlation of the diffraction pattern of the scattered field, and hence to the crosscorrelation of signals received at spaced antennas. An estimation method based on the latter enables measurement not only the horizontal wind field and the lateral diffraction pattern scales as seen at the receiver antennas, RADIO SCIENCE, VOL.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper the FCA algorithm and method described by Holloway et al [1997aHolloway et al [ , 1997b are used with six differing spaced antenna configurations to determine the consistency of estimating horizontally anisotropic three-dimensional refractive index perturbation scales.…”
Section: Introductionmentioning
confidence: 99%